2021
DOI: 10.3390/agronomy11102023
|View full text |Cite
|
Sign up to set email alerts
|

Parthenocarpy and Self-Incompatibility in Mandarins

Abstract: Citrus reproductive biology is complex. One of its characteristic features is parthenocarpy that enables seedless fruit production. Citrus parthenocarpy and self-incompatibility knowledge is only partial and sometimes discrepant. Increasing such knowledge is relevant for better managing cultivated varieties and improving the selection of parents in breeding strategies to recover seedless varieties such as mandarins. This work develops an efficient protocol to characterize self-incompatibility and different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 68 publications
2
24
0
1
Order By: Relevance
“…Self-incompatibility, also known as self-sterility, is a mechanism that rejects their self-pollen and inhibits seed formation in the absence of cross-pollination ( Montalt et al, 2021 ). Molecular studies revealed that genes within the S-locus, including S-RNase, SRK, and SLG, regulate the SI system ( Kachroo et al, 2002 ; Wang et al, 2009 ; Liang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-incompatibility, also known as self-sterility, is a mechanism that rejects their self-pollen and inhibits seed formation in the absence of cross-pollination ( Montalt et al, 2021 ). Molecular studies revealed that genes within the S-locus, including S-RNase, SRK, and SLG, regulate the SI system ( Kachroo et al, 2002 ; Wang et al, 2009 ; Liang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The over-expression of OsAAE3 in rice results in programmed cell death (PCD) and, consequently decreases pollen fertility ( Liu et al, 2017a ). Seedlessness in citrus has been reported to be associated with ovule sterility or self-incompatibility (SI; Montalt et al, 2021 ). SI system prevents self-fertilization by rejecting self-pollen in the style of flowering plants ( Claessen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological changes may change over time and can induce different responses to the SI reaction in some genotypes. For example, in a previous work [46], we classified 'Imperial' mandarin and 'Ellendale' tangor as non-strict self-incompatible genotypes because they produced both seedless and low-seeded fruit from self-pollinated flowers, which suggests an impact of environmental conditions [90]. Similarly, Claessen et al [12] indicated in pear and apple that the strength of the SI reaction differed depending on distinct intrinsic and extrinsic factors, including flower age and quality, temperature and application of plant hormones.…”
Section: Discussionmentioning
confidence: 96%
“…Several mechanisms have been described in citrus that, when coupled with parthenocarpy, produce seedless fruit; these include for example, ovule sterility in flowers with no functional pistils [35], degeneration [36] and chromosome aberrations in the embryo sac [37], stenospermocarpy [38,39], gene-cytoplasmic interaction [40], gamma irradiation [41,42] and triploidy [43][44][45]. Besides all these mechanisms, SI is also an efficient way to produce seedless genotypes [43,46]. The most important self-incompatible horticultural citrus groups are pummelos (Citrus maxima (Burm.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation